Ewangelia regułą życia osób konsekrowanych w nauczaniu Kościoła od Pawła VI do Franciszka - Małgorzata Pagacz (Polonia Sacra, 2022)
This article presents the importance of the Gospel in the life of consecrated persons according to the teaching of the Church from Paul VI to Francis. The teaching of Popes Paul VI, John Paul II, Benedict XVI and Francis point to the Gospel as the norm and rule of consecrated life. There are many points of convergence in the teaching of the post-conciliar popes on the evangelical character of the consecrated life. This issue is a clear example of the continuity of the teaching of the Church. Each of the Popes emphasizes their thought slightly differently, but they all unequivocally demand that consecrated persons be fully faithful to the Gospel. Because of the contemporary crisis of the consecrated life, these recommendations acquire particular significance and constitute a necessary signpost for the future.